Tinjauan terhadap Pengelolaan Perbatasan menurut Perspektif Hukum Internasional - Ni Made Risma Damayanthi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The management of national border areas is a strategic issue in the modern international system, directly linked to sovereignty, national security, and regional stability. This study aims to examine the role of international law in border management through a qualitative literature-based approach. Findings indicate that core principles of international law, such as uti possidetis juris, state sovereignty, and non-intervention, serve as the normative foundation for boundary formation, recognition, and dispute resolution. Current challenges such as illegal immigration, infiltration, and territorial claims demand the strengthened implementation of international law within national policy. Local government involvement and economic diplomacy also play vital roles in building adaptive and responsive border governance. In Indonesia’s case, land and maritime border dynamics highlight the need for a comprehensive strategy that integrates legal, diplomatic, and regional development aspects. This study underscores the importance of synergy among state actors to safeguard territorial integrity and foster sustainable cross-border cooperation.